Three distinct fiber pathways of the bed nucleus of the stria terminalis to the amygdala and prefrontal cortex. (May 2015) - Krüger, Oliver; Shiozawa, Thomas; Kreifelts, Benjamin; Scheffler, Klaus; Ethofer, Thomas
Abstract: The bed nucleus of the stria terminalis (BNST) is an important relay for multiple cortical and subcortical regions involved in processing anxiety as well as neuroendocrine and autonomic responses to stress, and it is thought to play a role in the dysregulation of these functions as well as in addictive behavior. While its architecture and connection profile have been thoroughly examined in animals, studies in humans have been limited to post-mortem histological descriptions of the BNST itself, not accounting for the distribution of its various connections. In the current study, we used diffusion-weighted magnetic resonance imaging (DW-MRI) to investigate the courses of fiber tracks connected to the BNST in humans. We restricted our seed region for probabilistic fiber tracking to the dorsal part of the BNST, as the ventral BNST is not distinguishable from the surrounding grey matter structures using magnetic resonance imaging. Our results show two distinct pathways of the BNST to the amygdala via the stria terminalis and the ansa peduncularis, as well as connections to the hypothalamus. Finally, we distinguished a route to the orbitofrontal cortex (OFC) running through the head of the caudate nucleus (CN) and the nucleus accumbens (NAcc). Pathways to brainstem regions were found to show a considerable inter-individual variability and thus no common pathway could be identified across participants. In summary, our findings reveal a complex network of brain structures involved in behavioral and neuroendocrine regulation, with the BNST in a central position.